Pendampingan Pengelolaan Investasi Keuangan Bagi Pelaku UMKM Sebagai Dukungan Fungsi Ekonomi Hijau - Saputri, Ika Puji; Fathihani, Fathihani; Randyantini, Vely (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
The lack of knowledge of MSME actors regarding the concept of green investment means that MSME actors are unable to implement business governance that supports green investment. Therefore, our community service team is trying to help with the problems currently being faced by MSMEs in the Tanjung Duren area, West Jakarta. The first is that we collaborate with MSME players in the Tanjung Duren area to understand financial planning and management well. Second, after the players understand financial management well, we provide solutions to MSME players to choose the right type of investment according to their abilities, especially green investments. Third, provide education on the benefits of green investment that will be felt by MSMEs. Collaboration partners for this activity are 20 MSME Business Actors (Age 20-30 Years) in the Tanjung Duren area, West Jakarta.This method of implementing community service is carried out by providing counseling to the participants in the form of lectures. The method of implementing community service consists of three stages, namely preparation, implementation and evaluation. The results of PkM activities show that MSME actors in the Tanjung Duren area can understand investment, especially green investment. It is hoped that this will give birth to an investment-conscious generation and make Indonesia an investment destination that is friendly to the environment, social and sustainable governance, especially for MSMEs.